Efficacy of focused ultrasound ablation surgery in patients with adenomyosis and coexisting pelvic adhesions - Jinfeng Lin; Zhiyun Yang; Lu Wang; Zhibo Xiao; Tao Tan; Jinyun Chen (International Journal of Hyperthermia)
Objective The objective of this study was to assess the efficacy of focused ultrasound ablation surgery (FUAS) in treating patients with adenomyosis and coexisting pelvic adhesions.Materials and methods A total of 396 patients diagnosed with adenomyosis and who underwent FUAS between January 2014 and December 2022 were enrolled. Pelvic adhesions were evaluated using magnetic resonance imaging (MRI), and the patients were categorized into either adhesive group or non-adhesive group. The aim was to investigate the comparative efficacy between the two groups.Results Among the 396 patients, pelvic adhesions were detected in 123 (31.06%) women. Compared to the non-adhesive group, patients in the adhesive group exhibited a higher preoperative dysmenorrhea score (7 vs. 6, p  < 0.001), a lower short-term clinical success rate (74.80% vs. 84.62%, p = 0.025), and a higher long-term cumulative recurrence rate (log-rank p = 0.009). The adhesive group exhibited a high incidence of anal discomfort during the procedure compared to the non-adhesive group (18.70% vs. 7.69%, p = 0.002). Additionally, patients with severe adhesion demonstrated a lower ratio of non-perfused volume ratio (NPVR) (38.81% vs. 46.58%, p = 0.009). Multivariate binary logistic regression analysis revealed that pelvic adhesion independently increased the risk of dysmenorrhea (OR = 4.730, 95%CI: 2.026–11.044, p < 0.001), while severe pelvic adhesion was identified as an independent risk factor for NPVR (OR = 2.226, 95%CI: 1.181–4.196, p = 0.013).Conclusion The preoperative assessment of pelvic adhesions plays a crucial role in predicting intraoperative adverse events of FUAS in patients with adenomyosis, as well as determining both short-term and long-term efficacy, thereby providing valuable guidance for the development of comprehensive treatment.